2023
DOI: 10.1108/reps-10-2022-0075
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and shadow economy: a panel analysis for Africa

Folorunsho M. Ajide,
James T. Dada

Abstract: PurposeThe study's objective is to examine the relevance of globalization in affecting the size of the shadow economy in selected African nations.Design/methodology/approachTo do this, the authors employ the KOF globalization index and implement both static and dynamic common correlated mean group estimators on a panel of 24 African nations from 1995–2017. This technique accommodates the issue of cross-sectional dependence, sample bias and endogenous regressors. Panel threshold analysis is also conducted to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…In the case of control variables, we find that GDPgr, FDI, and EXPEND have a strong and negative influence on the magnitude of activities in the shadow economy, whereas the variables URBA, and KOFGI seem to exert a strong positive effect on the growth of activities in the shadow economy. Earlier research identified associations between the shadow economy and similar variables, such as Ajide and Dada [ 15 ], Tran, Tran [ 73 ], Huynh and Nguyen [ 86 ], Ajide and Adeniyi [ 87 ] and Kireenko and Nevzorova [ 88 ].…”
Section: Results and Robustness Checksmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of control variables, we find that GDPgr, FDI, and EXPEND have a strong and negative influence on the magnitude of activities in the shadow economy, whereas the variables URBA, and KOFGI seem to exert a strong positive effect on the growth of activities in the shadow economy. Earlier research identified associations between the shadow economy and similar variables, such as Ajide and Dada [ 15 ], Tran, Tran [ 73 ], Huynh and Nguyen [ 86 ], Ajide and Adeniyi [ 87 ] and Kireenko and Nevzorova [ 88 ].…”
Section: Results and Robustness Checksmentioning
confidence: 99%
“…(4) Government expenditure (EXPEND), measured as the general government’s final consumption expenditure as a percentage of GDP [ 73 ]. (5) KOF Globalization Index (KOFGI) so as to measure globalization [ 15 , 17 , 77 ]. (6) Social progress is measured by the Human Development Index (HDI) [ 3 , 78 ].…”
Section: Dataset and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Former research related to the Trade Based Money Laundering that relevant to this research is presented as follows Globalization and shadow economy: a panel analysis for Africa (Ajide & Dada, 2023), research results showed that globalization reduces the size of the shadow economy. The results of the nonlinear analysis showed that there was a U-shaped relationship.…”
Section: Previous Researchmentioning
confidence: 99%